Seeds characters, pollen fertility and flavonoids of ten Brassicaceae collected near a kilns thermal power plant for air pollution bioindication - MITRA NOORI; ZAHRA BAGHAEIFAR; ABDOLKARIM CHEHREGANI; FARZANEH FARAKI (Nusantara Bioscience, 2018)
Noori M, Baghaeifar Z, Chehregani A, Faraki F. 2018. Seeds characters, pollen fertility and flavonoids of ten Brassicaceae collected near a kilns thermal power plant for air pollution bioindication. Nusantara Bioscience 10: 96-104. Shazand Steam Power Plant located on North-East of Shazand, Iran began to work from 2000. The power plant necessity fuel is natural gas and mostly heavy fuel oil. The most pollutant of power plant is sulfur compounds in addition to nitric and carbon mono oxide. Because environmental pollutants influence plant fertility and chemical compounds, therefore this study was done on ten wild Brassicaceae (Alyssum linifolium var. linifolium, Alyssum longistylum, Alyssum marginatum, Choriospora persica, Clypeola lappacea, Conringia perfoliata, Descurainia sophia, Goldbachia laevigata, Isatis kotschyana and Neslia apiculata) taxa collected from the thermal power plant area for bioindication of regional air pollution comparing to controls collected 40 km away from the power plant. Brassicaceae members are important for their ecological, pastoral, medicinal and edible points. Seed width and length max. and their ratio and abnormal seed percentage were calculated. Pollen abnormality and sterility percentages determined using Muntezing’s acetocarmine and light microscopy. Also, their pollen flavonoids were semi-quantitatively assessed using two-dimensional paper and thin layer chromatography. Results showed seeds health and their dimensions reduction in polluted samples in comparison with controls. In C. lappacea significant differences of seed and pollen abnormality and pollen sterility percentages, morin and kaempferol concentrations, between control and polluted samples were observed (P?0.05). Also, number and kind of pollen flavonoid changes especially increasing flavonoid contents were observed in polluted plants comparing to control. Studying seed and pollen characters can be used as air quality bioindicators.